One Step Towards a Green Environment: Education on Dry and Wet Waste Sorting and Innovation in Low-Smoke Combustion - Angelica Maulani Poetri Chantika; Muhamad Isya Ar-Rasyid; Muhammad Izaaz Mughoffar; Najya Nurul Aulia; Philana Zulfah Rachmawati; Siti Muslikah (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2026)
This study aims to examine strategies and community actions in fostering a green environment as part of ecological sustainability efforts. A green environment is conceptualized as a lifestyle emphasizing ecological awareness, wise resource management, and the reduction of negative impacts on nature. The study employed a qualitative descriptive approach through observation, interviews, and documentation with a local community actively engaged in environmental initiatives. The findings reveal that simple practices such as waste management, tree planting, and reducing plastic usage significantly improve environmental quality while fostering ecological awareness among community members. The main challenges identified include inconsistent eco-friendly behavior, limited waste management infrastructure, and insufficient support from local policies. Practical implications highlight the need for continuous environmental education, strengthening youth involvement as agents of change, and integrating eco-friendly programs into local development policies. Contribution: This study contributes to the academic discourse on the relationship between social behavior, ecological awareness, and sustainability, while offering a community-based model for environmental movements that can be replicated in various social contexts.